Facilitation of agricultural skills for promoting future careers of special students at Phrae Panyanukul School in Phrae Province - Poungsuk, P.; Kruadsungnoen, C.; Junlex, P. (My University, 2022)
Research findings showed that the agricultural teaching modules on laying hen farming, catfish farming, vegetable growing, quail farming and agricultural yield processing could develop agricultural skills of the students at a moderate up to a highest level. The data collection in the past 5 years found that the students preferred and developed the agricultural skills in activities on laying hen farming the most (64.80%). Overall, about 40% of the students had a good level of agricultural skills ( x =3.52; S.D =1.452). Only 11.27% needed teacher's suggestions and prompting on agricultural practice. It was found that the student's learning achievement after the promotion was higher than before, with a statistically significant difference level at 0.05. Most of the students (80.28%) could do farming well with their parents, while only 8.45% could do farming independently. Parents of the students were satisfied with agricultural skill development of the students at a high level ( x =3.65; S.D.=0.308); with the highest level of reason due to its being diverse and continual to gain experience in agricultural career ( x =4.54; S.D.=0.581). For problems encountered after graduation, most of the students lacked of continuity in agricultural careers and agricultural development (65.50%). For suggestions about agricultural skill development, teaching and learning activities should be arranged in small size. Furthermore, diverse agricultural skills should be promoted to benefit in the daily life activities of the students (90%).
Keywords: Agricultural skills; Future careers; Learning achievement; Self-reliant; Special students